Towards comprehensive understanding of proton-exchange membrane fuel cells using high energy x-rays. (12th May 2021) - Martens, Isaac; Chattot, Raphael; Wiegmann, Tim; Fuchs, Timo; Magnussen, Olaf M; Dubau, Laetitia; Maillard, Frederic; Drnec, Jakub
Abstract: For a future hydrogen economy, the development of cost effective energy conversion devices is a key issue. In this perspective, we discuss the use of high energy x-rays for obtaining comprehensive insights into the complex processes which occur inside such devices, focusing on proton exchange membrane fuel cells. This probe enables structural characterisation under operating conditions on all relevant length scales, from the atomic-scale interfaces to complete stacks. This opens up possibilities to go beyond characterisation of the isolated components, towards an understanding of their interactions in the full system which determine the power output, efficiency and degradation pathways in operational devices.